Thermodynamic Assessment of Coating Materials for Solid-State Li, Na, and K Batteries - Yu, Seungho; Park, Haesun; Siegel, Donald J. (American Chemical Society, 2019)
The development of all-solid-state batteries (ASSBs) presents a pathway to enhance the energy density and safety of conventional Li-ion batteries that use liquid electrolytes. However, one of the more promising categories of solid electrolytes (SEs), sulfides, are generally unstable in contact with common electrode materials, resulting in SE decomposition and high interfacial resistance. Recent studies have indicated that the application of coatings can, in some cases, stabilize the electrode/SE interface, reducing the likelihood for harmful interfacial reactions. Here, stable coatings for Li, Na, and K ASSBs are identified. In total, the stability windows for 1112 ternary alkali-metal-based compounds were assessed, including fluorides, chlorides, oxides, sulfides, phosphides, and nitrides. In general, the fluorides and chlorides exhibit the highest oxidative stability, suggesting that they are good choices for stabilizing SE/cathode interfaces. In contrast, sulfides, phosphides, and nitrides exhibit much lower oxidative stabilities, with many of these materials predicted to decompose above 2 V. At the anode/SE interface, nitrides and oxides are predicted to be the most effective coatings, as they are generally the most stable against reductive decomposition. As expected, sulfides and phosphides are the least stable class of materials under reducing conditions. Overall, oxides appear to be the most versatile class of coating materials: several oxides are predicted to exhibit stability windows ranging from 0 to 3 V with respect to Li/Li+, Na/Na+, or K/K+. Examples of promising oxides for stabilizing the SE/anode interface include Li5AlO4, Li4SiO4, NaAlO2, Na3PO4, KAlO2, and K3PO4. Similarly, promising compounds for stabilizing the SE/cathode interface include NaPO3 and KPO3. Finally, the possibility for kinetic stabilization suggests that additional ternary oxides (e.g., based on Ga, Nb, Sb, and Ta) may be viable coatings at the SE/cathode interface.
Keywords: DENSITY-FUNCTIONAL THEORY; 1ST PRINCIPLES; HIGH-ENERGY; STABILITY; ELECTROLYTE; 1ST-PRINCIPLES; CHALLENGES; INTERFACES; CONDUCTION; INSIGHTS